Canine Vector-Borne Diseases (CVBDs) in Liguria, North-West Italy: A Retrospective Study over an 11-Year Period (2013–2023) - Sara A. Chiarlone; Aitor Garcia-Vozmediano; Valentina Virginia Ebani; Nicola Pussini; Monica Dellepiane; Lisa Guardone; Elisabetta Razzuoli (Animals)
Canine vector-borne diseases (CVBDs) pose a global threat to both canine and public health. This study evaluates the prevalence of Anaplasma spp., Ehrlichia spp., Borrelia burgdorferi sensu lato (s.l.), Rickettsia conorii, and Dirofilaria immitis in domestic dogs in Liguria, north-west Italy, a region where data were lacking. From 2013 to 2023, 8584 blood samples from shelter (74%) and owned dogs (26%) were submitted to the Istituto Zooprofilattico Sperimentale of Piemonte, Liguria and Valle d’Aosta (IZSPLV) for serological testing (indirect immunofluorescence and/or rapid immunochromatographic tests). Overall, 18.8% (95% CI: 18.0–19.7) of the dogs tested positive for at least one pathogen, with positivity against R. conorii antigen being the most frequently recorded (24.4%, 95% CI: 23.3–25.5). Lower prevalence levels were observed for Anaplasma spp. (1.82%, 95% CI: 1.47–2.23), Ehrlichia spp., (1.25%, 95% CI: 0.97–1.60), B. burgdorferi s.l. (0.22%, 95% CI: 0.11–0.39), and D. immitis (0.84%, 95% CI: 0.65–1.06). Positive cases for all pathogens increased over time, with prevalence differing significantly between owned and shelter dogs. Topographical factors, land use, and monthly relative humidity appeared to influence the positivity in the dogs. These results update the epidemiology of the investigated CVBDs in Liguria, indicating a widespread exposure to Rickettsia spp. among local dogs.